Issues in pakistan's economy. - Zaidi, S. Akbar (Karachi : Oxford University Press, 2005)
This book is the main text for post-graduate courses on South Asia's development, economic history and on its political economy. For researchers on Pakistan's economy, it is the key source for reference, and covers a huge and diverse array of data, literature reviews, commentary and analysis. -- Publisher description.
Includes bibliographical references and Index.
Keywords: Economic history; Pakistan Economic policy